Emergence and development of ethno and cross-cultural perspectives on mental health/illness in Mexico, Brazil and Argentina in the second half of the 20th century - Silveti, Laurencia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In this research we address the emergence of ethno- and transcultural perspectives in mental health research in Latin America since the second half of the 20th century, taking as axes of analysis the developments of ethnopsychology of Rogelio Díaz-Guerrero in Mexico and the transcultural psychiatry of Álvaro Rubim de Pinho in Brazil and Fernando Pages Larraya in Argentina. The purpose of the work will be to explore and understand the emergence, development, permanence and contradictions of these perspectives, paying attention to the cognitive, social and institutional aspects that conditioned their development (context of production of the works, the epistemic communities that sustained them and the theoretical-methodological contents they produced). The research has a descriptive-interpretative exploratory character, in a qualitative design, from the perspective of Critical Discourse Analysis. The approach focuses on archival work, characterization and documentary analysis of the significant works of these authors and their research groups, according to the dimensions described. The advances produced so far allow us to see that these works, which are usually recognized as non-dogmatic, have in common several concerns that motivate the study of the relationship between culture and mental health-illness in reaction to the dominant ethnocentrism. These concerns range from the difficulties posed by the methodology of psychiatric diagnosis and specific problems in the clinic -especially in public services- that challenge the psychiatrist, to slippages related to certain national identity constructions and essentialisms posed by some of their hypotheses when incorporating the dimension of culture. This allows us to identify the ways in which the forms of knowledge produced affect, transform and invent statements about human experiences and how this knowledge is socially integrated.